ChemInform Abstract: Synthesis and Biological Evaluation of Carbohydrate Appended Hydrazinocyclopentenes with Potent Glycation and α‐Glucosidase Inhibition Activities. Issue 6 (11th February 2014) - Ajish, K. R.; Joseph, Nayana; Rani, M. Priya; Raghu, K. G.; Vineetha, V. P.; Radhakrishnan, K. V.
Abstract Synthesis and biological evaluation of novel alkylidenecyclopentene glycohybrids like (IV) are described.